ATP-binding cassette transporters and drug resistance in cutaneous leishmaniasis - Marina B.R. de Santana; Giulia O. Miranda; Lucas P. Carvalho (International Journal of Infectious Diseases)
Leishmania spp. are intracellular protozoan parasites causative of visceral and cutaneous leishmaniasis. Recognized as a neglected tropical disease affecting millions of people around the world, this affliction represents a major public health problem. In Brazil, pentavalent antimony (SbV), the main therapy used to treat all clinical forms of leishmaniasis, has become increasingly associated with treatment failure. Many factors can influence leishmaniasis treatment outcome, including low expression aquaglyceroporin by the parasite and high activity of the ATP-binding cassette (ABC) transporters, efflux pumps whose activity has been associated with drug resistance in a variety of diseases. Current evidence suggests that some ABC transporters (e.g., MRP1 and MDR1) play a role in drug resistance in leishmaniasis. One way to potentially overcome SbV resistance may be a combined therapeutic strategy involving anti-Leishmania drugs administered together with ABC transporter inhibitors; however, toxicity poses a major challenge to the adoption of this approach.